Hinduism to Christianity: An Anthropological Linguistics Study of Language Change in Buduk Village, Bali - Putra, I Komang Sumaryana (Humanis; Vol 28 No 4 (2024)DO - 10.24843/JH.2024.v28.i04.p02, 2024)
How does conversion of Hinduism to Christianity affect the language use and the switch of mother tongue in Buduk village? This is the question that this research was aimed at, through investigating the dynamic conditions of speakers from an anthropological linguistics perspective. This study used a combination of qualitative and quantitative methods with interviews, surveys, and observation, through statistical, discourse, and comparative analysis. The results showed that conversion of Hinduism to Christianity has influenced language use that ultimately leads to language change in various ways, such as the naming system, spontaneous language, and the language use in Christianity religious practices. This study contributes to the field of anthropological linguistics by providing insights on the complex interplay of religion, language, and culture in Buduk village.